2021
DOI: 10.1007/s00170-021-07744-6
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the corrosion behavior of AISI 304L stainless steel by deep rolling treatment under cryogenic cooling

Abstract: The effects of deep rolling parameters; particularly, work speed and cooling conditions (dry and cryogenic) on the surface integrity of AISI 304L machined samples and their further impact on uniform and localized corrosion behavior in chloride environment were experimentally investigated in this work. The electrochemical behavior of machined and deep rolled samples was assessed using cyclic potentiodynamic polarization tests in synthetic seawater. Findings of this study exhibit that grain refinement generated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 45 publications
2
3
0
Order By: Relevance
“…On Figure 7a the mean Ra values and their respective standard deviation are presented, for some levels of n an increase on burnishing speed tends to reduce the Ra values. For a single burnishing pass, an increase on burnishing speed, from 10 2 to 10 3 and from 10 3 to 10 4 mm/min, induces a decrease on Ra values, respectively to 0.15; 0.13 and 0.12 µm, this behavior is like the one observed by Gharbi et al [13]. The roughness profile however did not change significant as indicated by Figure 7b.…”
Section: Influence Of Burnishing Parameters On Roughness Valuessupporting
confidence: 77%
See 3 more Smart Citations
“…On Figure 7a the mean Ra values and their respective standard deviation are presented, for some levels of n an increase on burnishing speed tends to reduce the Ra values. For a single burnishing pass, an increase on burnishing speed, from 10 2 to 10 3 and from 10 3 to 10 4 mm/min, induces a decrease on Ra values, respectively to 0.15; 0.13 and 0.12 µm, this behavior is like the one observed by Gharbi et al [13]. The roughness profile however did not change significant as indicated by Figure 7b.…”
Section: Influence Of Burnishing Parameters On Roughness Valuessupporting
confidence: 77%
“…These authors also observed a grain refinement on a layer of 50 60 µm, which presented micro-sized grains. Grain refinement was also detected by Gharbi et al [13] that observed ultra-refined grains at the deep rolled AISI 304L surface, the altered layer presented a region with indistinct grain boundaries. Surface hardening and microstructural change on stainless steel after deep rolling was also observed by Muoz-Cubillos et al [14], these authors noticed strain hardening up to 340 µm of depth on AISI 304 steel, with the surface hardness increase reaching 157 HV 200g for the highest deep rolling force used (492 N).…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…In recent years, many studies have been devoted to improving the surface integrity (SI) and operating behavior (wear, corrosion and fatigue resistance) of CNASS components by means of static SCW methods: ball burnishing [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], roller burnishing [6,[22][23][24][25] and DB [2][3][4][26][27][28][29][30][31][32][33][34][35]. There are relatively few studies devoted to improvement in the fatigue behavior of CNASS components by means of SCW [2][3][4][8][9][10][11][12][13]18,23].…”
Section: Introductionmentioning
confidence: 99%